Cisi bohaterowie lat wojny i okupacji – rzecz o szkole, której nie było - Stefańska, Dorota (Biuletyn Szadkowski, 2010)
This contribution aims to recreate the picture of underground educational activity in Szadek and its neighborhood during the period of German occupation in Poland (1939– 1945). The information has been collected through interviews with the inhabitants of Szadek. It presents the persons who played outstanding roles in teaching Polish children and young people despite the severe punishment that it might entail. September 1939 was the beginning of the invaders’ educational policy, designed to eliminate Polish intelligentsia and to destroy Polish education and culture. Very soon Polish schools in Szadek, Przatów, Wilamów and Rzepiszew were closed. The teachers who remained in Szadek, despite being dislodged from their homes, showed great courage and dedication to secret teaching of Polish children. Under the pretext of teaching German they taught Polish, history, geography and mathematics. The persons who rendered the greatest services in this field in Szadek were: Helena Nawrocka, Olga Chominówna, Zofia Rutkowska and postman Kazimierz Sadowski.